Implementing of the BOPPPS Model on Basic Properties of Fractions Using Hawgent Dynamic Mathematics Software in Elementary Education - Wen, Zhuoya; Tang, Jianlan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2022)
The rapid development of information technology, informationization of education has become inevitable. Starting from the necessity of information-based teaching, this paper introduces the basic structure of the BOPPPS model and analyzes the content of each stage of the model. On this basis, the BOPPPS model is applied to the teaching of basic properties of fractions with the help of Hawgent dynamic mathematics software, in order to provide a theoretical basis for teachers to improve the teaching and methods of elementary mathematics, enhance the efficiency of classroom teaching, and help the implementation of